2010
DOI: 10.2113/gsrocky.45.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphic evaluation of reservoir and seal in a natural CO2 field: Lower Paleozoic, Moxa Arch, southwest Wyoming

Abstract: The Moxa Arch in the Greater Green River Basin, southwestern Wyoming, hosts two potential reservoirs for CO 2 sequestration. The Bighorn Dolomite and Madison limestone are interpreted to be independent reservoirs based on differing CO 2 compositions and production histories; the two reservoirs are separated by Devonian carbonates, siliciclastic rocks, and evaporites. On the Moxa Arch, the Bighorn ranges in thickness from 67 to 120 m with porosities from 3 to 15 percent. The massive buff-colored Steamboat Point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…An estimated volume of former anhydrite nodules in the drill cores of 0.2 vol% would equate to 2.55 × 10 9 m 3 or 5.6 × 10 13 mol in the reservoir. The amount of CO 2 is estimated to be 3.15 × 10 +12 m 3 STP (De Bruin, 1991;Lynds, 2010). Based on an assumed CO 2 -H 2 S ratio of 1:13 (gas composition of 65% CO 2 and 5% H 2 S; Huang et al, 2007) and this CO 2 volume, the H 2 S gas volume is calculated to be 2.4 × 10 11 m 3 or 9.8 × 10 12 mol.…”
Section: Sulfur Cycling and Duration Of Tsrmentioning
confidence: 99%
See 1 more Smart Citation
“…An estimated volume of former anhydrite nodules in the drill cores of 0.2 vol% would equate to 2.55 × 10 9 m 3 or 5.6 × 10 13 mol in the reservoir. The amount of CO 2 is estimated to be 3.15 × 10 +12 m 3 STP (De Bruin, 1991;Lynds, 2010). Based on an assumed CO 2 -H 2 S ratio of 1:13 (gas composition of 65% CO 2 and 5% H 2 S; Huang et al, 2007) and this CO 2 volume, the H 2 S gas volume is calculated to be 2.4 × 10 11 m 3 or 9.8 × 10 12 mol.…”
Section: Sulfur Cycling and Duration Of Tsrmentioning
confidence: 99%
“…paucity of petrographic observations from the LaBarge Field. The gas forms a 250-m-thick gas column and is the largest known natural CO 2 accumulation in the world (Allis et al, 2001;Lynds et al, 2010;Stilwell, 1989). Different sources for the CO 2 and H 2 S at the LaBarge Field have been proposed including thermal degradation of hydrocarbons, breakdown of carbonates, volcanic gas migration, and TSR (De Bruin, 2001;Huang et al, 2007;Stilwell, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…It is tempting to attribute this excursion to cratonic erosion that occurred with the widespread glaciation that developed in latest Famennian (Isaacson et al, 2008, Brezinski et al, 2010and McClung et al, 2013, resulting in increased 87 Sr input to the oceans (Clemens et al, 1993). Late Devonian basinal sediments that have local cratonic sediment sources may exhibit elevated 87 Sr/ 86 Sr values up to 0.71083 (Lynds et al, 2010), and continental weathering at the D-C boundary was exacerbated not only by changes in sea level but also the erosion of the rising Appalachians by glaciers (Brezinski et al, 2009). It has even been suggested that the tectonic uplift of the Appalachians alone could also have affected seawater 87 Sr/ 86 Sr ratios (Richter et al, 1992).…”
Section: Detection Of the D-c Boundarymentioning
confidence: 99%
“…The study area was chosen after being identified as having significant potential for geologic sequestration of impure CO 2 in a deep reservoir environment. Several formations were identified as potentially suitable for deep reservoir storage of impure CO 2 gas, foremost among them the Ordovician Bighorn Dolomite and the Mississippian Madison Limestone (for a more detailed description of the geologic characteristics and sequestration potential of the Moxa Arch anticline, see Lynds et al (2010)). This site was also of interest for sequestration research activities due to a large abundance of natural CO 2 being produced as a byproduct of oil and gas development in the region and an already present CO 2 sequestration infrastructure and market to support enhanced oil recovery (EOR).…”
Section: Study Areamentioning
confidence: 99%